Robust Magneto-Ionic Effect in Fe/FeOx Thin Films in Electrolytes With Different Cations - Zehner, J.; Vaerst, O.; Soldatov; Nielsch, Kornelius; Schaefer, Rudolf; Leistner, K. (IEEE Transactions on Magnetics, 2022)
Electrochemical reactions offer an elegant way to influence the magnetic properties of nanoscaled materials by applying a small voltage. The present study focuses on such magneto-ionic changes in thin Fe/FeOx films induced by interfacial electrochemical reactions in liquid electrolytes. The films are prepared by inclined sputter deposition and exhibit a uniaxial in-plane anisotropy. LiOH, NaOH, and KOH in an aqueous solution are used as electrolytes. The changes in the hysteresis loops and the magnetic microstructure are observed by in-situ Kerr microscopy. Upon low voltage application, the electrochemical reduction reaction leads to the transformation of the FeOx-layer into the metallic Fe. Simultaneously, a strong decrease of coercivity and remanence together with an increase of domain size occurs. These observations are in line with a previously reported magnetic de-blocking mechanism caused by the variation of Néel wall interactions during the oxide-metal transformation. When applying the oxidation potential, the coercivity, remanence, and domain size are re-established. The changes occur in a similar manner for all studied electrolytes and can be repeatedly achieved for multiple voltage switching steps. This evidences that the electrochemical reaction mechanism responsible for the magneto-ionic switching is very robust and dictated by the anion (OH-) rather than the type of cation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Functional materials; magneto-electric; voltage control of magnetic anisotropy; voltage control of magnetic domains